2006
DOI: 10.2337/dc06-0617
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcomes of Patients With Screen-Detected Type 2 Diabetes

Abstract: OBJECTIVE -The objective of this study was to investigate how time since diagnosis and treatment intensity influence psychological outcomes in patients with screen-detected type 2 diabetes.RESEARCH DESIGN AND METHODS -A 2 ϫ 2 factorial cross-sectional design was used to examine psychological outcomes in 196 patients with screen-detected diabetes diagnosed 3-33 months previously who were receiving usual care or intensive multifactorial pharmacological treatment. Outcomes included anxiety, depression, diabetes-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
8
48
0
Order By: Relevance
“…reported low anxiety, depression and diabetes related distress, regardless of the time since diagnosis (Thoolen, De Ridder, Bensing, Gorter, & Rutten, 2006). Overall, these studies confirm that screening has no long-term emotional effects for most patients, and only limited short-term effects.…”
Section: Screen-detected Patientssupporting
confidence: 61%
See 2 more Smart Citations
“…reported low anxiety, depression and diabetes related distress, regardless of the time since diagnosis (Thoolen, De Ridder, Bensing, Gorter, & Rutten, 2006). Overall, these studies confirm that screening has no long-term emotional effects for most patients, and only limited short-term effects.…”
Section: Screen-detected Patientssupporting
confidence: 61%
“…More than half felt confident that they could do something about their diabetes themselves by adjusting their diet and taking medication (Adriaanse et al, 2002). A study assessing self-efficacy among 196 screen-detected patients found that three-quarters reported a high confidence that they could manage their disease but significantly less were actually engaged in self-care (Thoolen et al, 2006). Finally, in interviews with eight screen-detected patients, associates (2007a, 2007b) found that all patients talked confidently about their ability to control the disease.…”
Section: Self-efficacy and Controllabilitymentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3][4] Controlled studies reported higher levels of anxiety in patients shortly after diagnosis with t2Dm compared with those of people not diagnosed as having the disease, but these raised anxiety levels were of short duration. [2][3][4] this minimal emotional response could be due to unawareness regarding the seriousness of the disease, which has a relatively mild, nonacute character in its early stages, but also to denial or indifference. 1 However, the exact causes for this lack of response are unclear.…”
Section: Introductionmentioning
confidence: 95%
“…In a study by Delahanty et al (2007), participants who were treated with insulin reported significantly more distress than participants who reported being treated with oral medications or dietary restrictions. Closely related, Thoolen, de Ridder, Bensing, Gorter, & Rutten (2006) observed an interaction between participants' treatment intensity and length of diagnosis. Within this study, intensely treated patients, such as those treated with insulin, reported more distress in the first year of diagnosis, while moderately treated patients, such as those prescribed oral agents, reported more distress 2-3 years following diagnosis.…”
Section: Disparities In Diabetes-related Emotional Distressmentioning
confidence: 81%